(untitled) (Research, Society and Development, 2021)
Interprofessional communication platforms have shown promise in the articulation between primary and specialized care. This article sought to analyze the health impacts resulting from the use of electronic communication systems between general practitioners and specialists. An integrative review was carried out in the BVS, PubMed and Scielo databases, and an analysis of gray literature in the Google Scholar platform, without a time filter. After applying the inclusion and exclusion criteria, 27 studies were selected. These were published between 2000 and 2020, were mostly Canadian studies, and had electronic systems developed for multiple specialties as predominant. Through a variety of approaches, the articles highlighted a reduction in referral rates to specialized care services, cost savings and improvement in the quality of health care provided by primary care as impacts resulting from the use of interprofessional communication platforms.